2021
DOI: 10.3390/en14185597
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Performance, Emission, and Combustion Characteristics of a Common Rail Direct Injection Diesel Engine Powered with Three Different Biodiesel Blends

Abstract: Biodiesel is a renewable energy source which is gaining prominence as an alternative fuel over fossil diesel for different applications. Due to their higher viscosity and lower volatility, biodiesels are blended with diesel in various proportions. B20 blends are viable and sustainable solutions in diesel engines with acceptable engine performance as they can replace 20% fossil fuel usage. Biodiesel blends are slightly viscous as compared with diesel and can be used in common rail direct injection (CRDI) engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In the present study, we referred to some of the literature based on different feedstock for biodiesel emission and performance data. For instance, Teja et al [7] reported B20 blends of three biodiesels derived from cashew nutshell (CHNOB (B20)), jackfruit seed (JACKSOB (B20)), and Jamun seed (JAMNSOB (B20)) oils. In the JAMNSOB (B20) blend, BTE and NO x increased by 4.04% and 0.56% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we referred to some of the literature based on different feedstock for biodiesel emission and performance data. For instance, Teja et al [7] reported B20 blends of three biodiesels derived from cashew nutshell (CHNOB (B20)), jackfruit seed (JACKSOB (B20)), and Jamun seed (JAMNSOB (B20)) oils. In the JAMNSOB (B20) blend, BTE and NO x increased by 4.04% and 0.56% respectively.…”
Section: Introductionmentioning
confidence: 99%